Increasing nitrate/ammonium ratio for improvement of garlic micropropagation - Luciani, Gabriela Fabiana (2001)
The effect of different culture media with different growth regulator and nitrate/ammonium ratios on split garlic shoots was studied to obtain an optimized micropropagation protocol. Three basal media: MS, BDS and BLM (i.e. BDS modified to obtain a nitrate:ammonium ratio of 35 mM:8 mM) combined with two concentrations of NAA (0.5 or 5 μM) and BAP (1 or 10 μM) were evaluated in three Colorado garlic clones: Español Selección Ascasubi (ESA), Español Selección Médanos (ESM) and I 50. In BLM medium with 5 μM NAA and 10 μM BAP the highest multiplication rates were 140, 542 and 743 shoots per split shoot after three subcultures in 140 days for clones ESA, ESM and I 50, respectively. Comparing the mean rates obtained in MS medium with those obtained in BDS medium in the same time, the latter produced 1.5-, 4- and 2.2-fold increases in the mean multiplication rates for ESA, ESM and I 50 clones, respectively; while BLM produced 5-, 3- and 10-fold increases in the mean multiplication rates. Since BDS and BLM media only differ in their NO3−:NH4+ ratio we can conclude that the differences in the multiplication rates could probably be due to an increase in the NO3− level of the BLM medium and so the multiplication ratios for these garlic clones can be greatly improved by the use of higher levels of nitrogen supplied as nitrate (35mMNO3−:8mMNH4+ ratio) with higher concentrations of growth regulators such as 5 μM NAA and 10 μM BAP.